POLA KOMUNIKASI INTERPERSONAL KIAI DENGAN SANTRI TAHFIDZUL QUR’AN DI PONDOK PESANTREN AL-HAROMAIN JEMBER - Khurrin Nabila; A. Khairuddin (Fakultas Dakwah Universitas Ibrahimy, 2025)
This paper reveals interpersonal communication between kiai and students of Tahfidzul Qur'an at Al-Haromain Islamic Boarding School, Jember. Good interpersonal communication is an important thing that must be done between students and kiai, this is because it is to create effective communication. This study uses a qualitative approach with a case study research type. The primary data sources of this study are kiai and students of Tahfidzul Qur'an at AlHaromain Islamic Boarding School, Jember. The secondary data sources are documentation and official archives. The data collection techniques used are observation, interviews, and documentation, and data analysis techniques. The results of this study indicate that the interpersonal communication patterns of kiai and students of Tahfidzul Qur'an are knowing memorization abilities, conducting group communication, providing motivation, being a role model in enthusiasm, using routine media rituals, being open to receiving improvements, always providing support if students have problems, encouragement to memorize consistently, encouragement to struggle to face difficulties in memorizing, communication with respect, communication with polite language and meaningful communication guiding and teaching.